Centrifugation versus filtration-based cell salvage: impact on perioperative bleeding in cardiac surgery—the COLTRANE randomised clinical trial – study protocol - Christine Mouton; Nicolas Nesseler; Antoine Bénard; Mathieu Pernot; Alexandre Ouattara; Antoine Beurton; Alexandre Mansour; Victor-emmanuel Brett; Corinne Batsale; Anais Aitgougam; Anais Cordon; Aurelie Fresselinat; et al. (BMJ Open, 2025)
Introduction Cardiac surgery remains a high-risk procedure for bleeding despite advances in patient blood management. Conventional centrifugation-based autotransfusion devices primarily recover red blood cells, losing platelets and coagulation factors. The SAME autotransfusion device (i-SEP, Nantes, France) introduces an innovative filtration-based approach, recovering erythrocytes, leucocytes and platelets to enhance perioperative haemostasis. The main objective is to determine whether the filtration-based SAME device reduces significant perioperative bleeding compared with the centrifugation-based system in high-risk cardiac surgery patients.Methods and analysis The Centrifugation-based vs filtration-based intraOperative cell saLvage on qualiTy of peRioperAtive haemostasis iN cardiac surgEry (COLTRANE) trial is a multicentre, parallel-group, single-blinded, superiority-randomised clinical trial. Conducted over 19 months in 10 French hospitals, the study will target patients at high risk of bleeding undergoing on-pump cardiac surgery via sternotomy. A total of 570 patients (285 per group) are required to achieve 80% statistical power for detecting clinically significant differences. Eligible patients will be randomised to either a centrifugation-based or filtration-based autotransfusion group. Both groups will follow standardised perioperative and cardiopulmonary bypass management, with the devices used only intraoperatively. The primary outcome is the proportion of patients with clinically significant perioperative bleeding defined as classes 2 to 4 of the Universal Definition of Perioperative Bleeding. The secondary outcomes include device efficiency and safety, perioperative haemostasis, lengths of intensive care unit and hospital stays, early postoperative morbidity and 30-day all-cause mortality. Ancillary studies will be performed to evaluate cell recovery and washing performance, the viscoelastic properties of retransfused blood (Quantra Qplus; Stago, Asnières-sur-Seine, France), and the effect of salvaged leucocytes on postoperative inflammation and immune function.Ethics and dissemination This trial has received a favourable opinion from the Committee for the Protection of Persons and authorisation from the French authorities (Comité de protection des personnes Nord Ouest, IDRCB: 2023-A02566-39). Protocol V.1.1 was approved on 22 January 2024. The trial is registered on ClinicalTrials.gov (NCT06425614). The findings will be disseminated through oral communications at national and international scientific meetings and peer-reviewed journal publications. Individual participant data will be made available on reasonable request to qualified researchers, following review and approval by the study sponsor and ethics committee.Trial registration number ClinicalTrials.gov, NCT06425614.